2020
DOI: 10.1155/2020/8825828
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Root Morphology on Rooted‐Soil Shear Resistance Using Triaxial Testing

Abstract: Mechanical reinforcement by plant roots increases the soil shearing strength. The geometric and distribution characteristics of plant roots affect the soil shearing strength. Current research on the shear strength of rooted-soil is mostly based on direct shear tests with a fixed shear surface and thus cannot reflect the actual failure state of the rooted-soil. In this study, Golden Vicary Privet was used to create a rooted-soil, and a triaxial test method was used for soil mechanical property analysis. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, it had little effect on the internal friction angle. Meng et al [22] drew the same conclusions from their experiments, and in most studies [36][37][38], the conclusions are basically the same.…”
Section: Shear Strength Of Root-soil Composite and Its Relationship W...mentioning
confidence: 68%
See 1 more Smart Citation
“…However, it had little effect on the internal friction angle. Meng et al [22] drew the same conclusions from their experiments, and in most studies [36][37][38], the conclusions are basically the same.…”
Section: Shear Strength Of Root-soil Composite and Its Relationship W...mentioning
confidence: 68%
“…Zheng et al [21] carried out shear tests on the rice root-soil complex on a universal material-testing machine with a self-made shear test device. Meng et al [22] performed mechanical analysis of soils containing Golden Vicary Privet roots, and they found that both root geometry and distribution characteristics affected the shear strength of rooted soils. Hou et al [23] studied the use of X-ray-computed tomography (CT) as a non-invasive method to detect root distribution in soil.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Patel and Singh (2020) found small increases in shear strength measured by triaxial test conferred to artificial mixtures of clayey and sandy sediments containing glass fibre reinforcement. Meng et al (2020) also observed variability in shear strength related to the rooting geometry of Golden Vicary Privet (Ligustrum spp.) in a controlled planting experiment and found that the root network's effect was largely to enhance the sediment cohesion rather than friction angle.…”
Section: Discussionmentioning
confidence: 83%
“…Generally, the most frequently used root arrangement patterns for the current research are vertical, horizontal, crossed, and mixed arrangements. There is a consensus that crossed and mixed arrangement patterns have a better reinforcement effect than vertical and horizontal distribution patterns 20,21 . On this basis, we chose crossed arrangement and mixed arrangement, which are more closely matched to the actual distribution, for the study comparison.…”
Section: Materials and Test Methodsmentioning
confidence: 99%
“…First, direct shear tests, as one kind of traditional strength test, have been widely used to investigate the reinforcement effect of different plant roots, and the results showed that the shear strength of root-reinforced soil has improved compared with that of plain soil by root enhancing the soil cohesion 14,15 . Data obtained by subsequent researchers through direct shear tests showed that root geometry [16][17][18][19] (root diameter and root length) and distribution characteristics 20,21 (root density and root distribution angle) had a significant effect on the shear strength of the soil. Second, triaxial compression tests are also commonly conducted to study the properties of root-reinforced soils.…”
mentioning
confidence: 99%